Yikes! Are we disgusted by politicians?. (29th September 2020) - Bakker, Bert N.; Schumacher, Gijs; Homan, Maaike D.
Abstract : In the political domain, disgust is primarily portrayed as an emotion that explains individual differences in pathogen avoidance. We hypothesized that political rhetoric accusing opponents of moral transgressions also elicits disgust responses. In this registered report, we present the results from a laboratory experiment. We find that participants self-report higher disgust and have stronger physiological (Levator labii) responses to pictures of out-party leaders compared with in-party leaders. Participants also report higher disgust in response to moral violations of in-party leaders. There is more suggestive evidence that in-party leaders evoke more labii activity when they commit moral violations than when out-party leaders do. The impact of individual differences in moral disgust and partisanship strength is very limited to absent. Intriguingly, on average, the physiological and self-reported disgust responses to the treatment are similar, but individuals differ in whether their response is physiological or cognitive. This motivates further theorizing regarding the concordance of emotional responses.